Low-frequency pulse profile variation in PSR B2217+47: evidence for echoes from the interstellar medium. Issue 2 (13th February 2018) - Michilli, D; Hessels, J W T; Donner, J Y; Grießmeier, J-M; Serylak, M; Shaw, B; Stappers, B W; Verbiest, J P W; Deller, A T; Driessen, L N; Stinebring, D R; Bondonneau, L; et al.
Abstract: We have observed a complex and continuous change in the integrated pulse profile of PSR B2217+47, manifested as additional components trailing the main peak. These transient components are detected over 6 yr at 150 MHz using the LOw Frequency ARray (LOFAR), but they are not seen in contemporaneous Lovell observations at 1.5 GHz. We argue that propagation effects in the ionized interstellar medium (IISM) are the most likely cause. The putative structures in the IISM causing the profile variation are roughly half-way between the pulsar and the Earth and have transverse radii R ∼ 30 au. We consider different models for the structures. Under the assumption of spherical symmetry, their implied average electron density is n_e 100 cm −3 . Since PSR B2217+47 is more than an order of magnitude brighter than the average pulsar population visible to LOFAR, similar profile variations would not have been identified in most pulsars, suggesting that subtle profile variations in low-frequency profiles might be more common than we have observed to date. Systematic studies of these variations at low frequencies can provide a new tool to investigate the proprieties of the IISM and the limits to the precision of pulsar timing.